Contemporary Dance As A Communication Media Between Generations Case Study: Empowering Family Welfare In Dadap Village, South Tangerang City - Nuriman, Dian Agustine; Octory, Gadis; Juliadi, Rismi (PT. Hafasy Dwi Nawasena, 2024)
Contemporary dance is a dance art that is popular with not only Generation Z but also the millennial generation, which is currently the age of parents who already have teenage children. The increasing problems in children and adolescents that occur today are often caused by a lack of good internal communication through interpersonal communication between parents and their children. As the growth of digital media consumption, especially social media, occurs in Indonesia, it also affects the lack of communication within the family or even between neighbors, making it difficult to communicate and coordinate with each other. Through this research, it is hoped that it can help mothers and young women to be able to make dance a medium of communication between generations to be able to create harmonious and useful collaborative activities in fostering communication not only for the smallest social environment, namely the family but also for the community of Dadap village residents to create harmonious relationships between residents, especially between generations.